2021
DOI: 10.1093/bib/bbab165
|View full text |Cite
|
Sign up to set email alerts
|

MDA-GCNFTG: identifying miRNA-disease associations based on graph convolutional networks via graph sampling through the feature and topology graph

Abstract: Accurate identification of the miRNA-disease associations (MDAs) helps to understand the etiology and mechanisms of various diseases. However, the experimental methods are costly and time-consuming. Thus, it is urgent to develop computational methods towards the prediction of MDAs. Based on the graph theory, the MDA prediction is regarded as a node classification task in the present study. To solve this task, we propose a novel method MDA-GCNFTG, which predicts MDAs based on Graph Convolutional Networks (GCNs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 231 publications
0
20
0
Order By: Relevance
“…In biological data analyses, there exist many topological structures such as gene-sharing network, disease-drug relationship graph, and diseases-gene relationship graph. Utilizing these relationships in GCN has led to several successful applications [21,22,23,24,25].…”
Section: Methodsmentioning
confidence: 99%
“…In biological data analyses, there exist many topological structures such as gene-sharing network, disease-drug relationship graph, and diseases-gene relationship graph. Utilizing these relationships in GCN has led to several successful applications [21,22,23,24,25].…”
Section: Methodsmentioning
confidence: 99%
“…So, I will be content with a few general reviews and some papers that I found particularly interesting or promising. The focus will be on methods that retain a structural/dynamic model where the role of ML is to accelerate calculations/simulations rather than the, equally meritorious, approach of data base searches, for example in the area of drug design (where we have made some recent contributions [126][127][128] ). Below, I will follow the bi-thematic approach adopted so far in this Tutorial Review with sights firmly set on complex materials and biological systems.…”
Section: Cell Biologymentioning
confidence: 99%
“…The final association prediction was equated to the recommendation task, and a matrix completion was applied to predict hidden MDAs. For predicting MDAs from a comprehensive and novel perspective, Chu et al [ 17 ] developed an original model (MDA-DCNFTG) based on the GCN, which treated MDAs prediction as a node classification task. The highlight of the MDA-GCNFTG was that it used graph sampling to predict MDAs from the perspective of feature and topological graphs based on Graph Convolutional Networks (GCNs).…”
Section: Introductionmentioning
confidence: 99%